2004
DOI: 10.1159/000076491
|View full text |Cite
|
Sign up to set email alerts
|

Successful Treatment of Cutaneous Langerhans Cell Histiocytosis with Thalidomide

Abstract: Langerhans cell histiocytosis (LCH) represents a group of rare histiocytic syndromes characterized by tissue infiltration with dendritic cells. The management of LCH is difficult as these disorders respond inconsistently to immunosuppressive and chemotherapeutic strategies. Thalidomide (N-phtalimidoglutarimide), initially used as a tranquilizer, has recently been used in the management of several inflammatory skin diseases. We describe the case of a 38-year-old male with mucocutaneous LCH. A treatment course w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 11 publications
1
25
0
Order By: Relevance
“…Thalidomide of 200 mg daily successfully treated cutaneous Langerhans cell histiocytosis in 38-year-old male [7].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Thalidomide of 200 mg daily successfully treated cutaneous Langerhans cell histiocytosis in 38-year-old male [7].…”
Section: Discussionmentioning
confidence: 98%
“…Thalidomide has shown beneficial effect in kaposi's sarcoma in HIV patients and in Human herpes virus-8-associated kaposi sarcoma following HSCT [6]. Thalidomide also exerts an antiproliferate effect against histiocytes [7]. In vitro, thalidomide inhibits TNF-a production by human monocytes and exerts an antiangiogenic effect by inhibiting vascular endothelial growth factor inhibition, basic-fibroblast growth factor, and IL-6 [4,5].…”
Section: Discussionmentioning
confidence: 99%
“…Originally, thalidomide was recognized for its role in the treatment of erythema nodosum leprosum; however, thalidomide’s effectiveness is now well documented in a variety of diseases including aphthous stomatitis, discoid lupus erythematosus, actinic prurigo, Behçet’s disease, prurigo nodularis, cutaneous Langerhans cell histiocytosis, vulvar ulcerations associated with Crohn’s disease and HIV-associated dermatological conditions[ 30, 34, 35]. …”
Section: Discussionmentioning
confidence: 99%
“…This led to the evaluation of thalidomide in the treatment of several cancers [1]. Thalidomide has recently been used in the management of several inflammatory skin diseases including scleromyxedema, cutaneous Langerhans cell histiocytosis, sarcoidosis or discoid lupus erythematosus [2, 3]. Several studies have suggested its interest for treating AIDS-related KS, but only anecdotal reports are available in non-HIV-related KS.…”
Section: Introductionmentioning
confidence: 99%